TD-92, a novel erlotinib derivative, depletes tumor-associated macrophages in non-small cell lung cancer via down-regulation of CSF-1R and enhances the anti-tumor effects of anti-PD-1. (1st February 2021) - Shih, Chi-Ting; Shiau, Chung-Wai; Chen, Yen-Lin; Chen, Li-Ju; Chao, Tzu-I; Wang, Cheng-Yi; Huang, Chao-Yuan; Hung, Man-Hsin; Chen, Kuen-Feng
Abstract: Recent advances in immune checkpoint inhibition, which augment T-cell immune responses, have highlighted the potential of exploiting one's immune system to combat cancer. However, only a relatively small number of non-small cell lung cancer (NSCLC) patients benefit from immune checkpoint blockade due to the immunosuppressive tumor microenvironment. Therefore, combination immunotherapies are now being developed to achieve maximal therapeutic benefits. In this study, we assessed whether a novel erlotinib derivative, TD-92, which possesses anti-tumor effects across several cancer cell lines, could enhance anti-PD-1 treatment. Our results demonstrated that the combined treatment of anti-PD-1 and TD-92 resulted in a potent anti-tumor response in a Lewis lung carcinoma cancer model, as evidenced by the reduced tumor growth and increased survival. Analysis of immune cell population counts revealed that TD-92 reduced the number of pro-tumorigenic CD11b + F4/80 + tumor-associated macrophages, without significantly affecting the total numbers of other major immunocytes. Further experiments showed that TD-92 induced a marked decline in colony stimulating factor 1 receptor (CSF-1R) expression in macrophage cell lines. The results also suggested that c-Cbl-mediated proteasome degradation was involved in TD-92-mediated CSF-1R downregulation. Our data paves the way for the development of additional combination immunotherapies for NSCLC patients. Highlights: TD-92, exerts anti-NSCLC activity through downregulating c-Myc via PP2A activation. TD-92 enhances anti-PD-1 immunotherapy through decreasing the presence of TAMs. TD-92 exerts stronger cytotoxicity against macrophage than pexidartinib. TD-92 elicits downregulation of CSF-1R via c-Cbl-mediated proteasomal degradation. Overexpression of CSF-1 is tumor specific in NSCLC patients.